2009
DOI: 10.1111/j.1365-2869.2008.00699.x
|View full text |Cite
|
Sign up to set email alerts
|

Sleep and sleep ecology in the first 3 years: a web‐based study

Abstract: SUMMARY This study was designed to provide data on sleep patterns during the first 3 years, based on a large US-Canada Internet sample, to assess the prevalence of parental interventions and related factors of infant sleep ecology and to evaluate the links between sleep ecology and sleep. Five thousand six parents completed a web-based online questionnaire about their children, aged from birth to 36 months. The questionnaire included items pertaining to sleep patterns, sleep environment, sleeprelated parental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

51
315
4
11

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 426 publications
(381 citation statements)
references
References 53 publications
51
315
4
11
Order By: Relevance
“…They often appear as difficulty getting children to bed in the evening, children taking a long time to fall asleep, and frequent episodes of awakening at night. It is known that children who develop sleep regulation, through “self-soothing” skills before falling asleep, often sleep in a more satisfactory way and have fewer episodes of awakening at night than do other children (Owens, Chervin, & Hoppin, 2017; Sadeh, Mindell, Luedtke, & Wiegand, 2009). Behavioural sleep problems in small children often involve the parents attempting to control sleep regulation in their children—such as by rocking them—or children becoming used to undesirable sleep-associated stimuli such as falling asleep with a bottle, so that they do not learn self-soothing before falling asleep.…”
Section: Introductionmentioning
confidence: 99%
“…They often appear as difficulty getting children to bed in the evening, children taking a long time to fall asleep, and frequent episodes of awakening at night. It is known that children who develop sleep regulation, through “self-soothing” skills before falling asleep, often sleep in a more satisfactory way and have fewer episodes of awakening at night than do other children (Owens, Chervin, & Hoppin, 2017; Sadeh, Mindell, Luedtke, & Wiegand, 2009). Behavioural sleep problems in small children often involve the parents attempting to control sleep regulation in their children—such as by rocking them—or children becoming used to undesirable sleep-associated stimuli such as falling asleep with a bottle, so that they do not learn self-soothing before falling asleep.…”
Section: Introductionmentioning
confidence: 99%
“…The study was approved by the local ethics committee. QUESTIONNAIRE The questionnaire was developed by two centres (İstanbul University and Gaziantep University) based on the significant variables found in a review of the previous literature on childhood sleep 8,11,[13][14][15][16] and was tested in a pilot study. The previous studies reported sleeping problems like bedtime resistance, number of night-time waking, difficulty in falling asleep, difficulty maintaining sleep, sleeping in the parental bed at night, sleep onset time, mean sleep duration at night, napping, daytime sleep duration, and total sleep duration.…”
Section: Methodsmentioning
confidence: 99%
“…The previous studies reported sleeping problems like bedtime resistance, number of night-time waking, difficulty in falling asleep, difficulty maintaining sleep, sleeping in the parental bed at night, sleep onset time, mean sleep duration at night, napping, daytime sleep duration, and total sleep duration. 8,11,[13][14][15][16] After receiving information on the aim of the study, then each parent completed the questionnaire. For illiterate parents, the nurse completed the questionnaire by interviewing the parents.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the concept of "normal sleep" varies according to cultural backgrounds. 27,28 In fact, one quarter of parents in predominantly Caucasian countries perceive that their child has a sleep problem. 28 Clinicians and parents will therefore benefit from a context-specific estimate of night-time sleep duration in relationship to various characteristics in this age group.…”
mentioning
confidence: 99%